2017
DOI: 10.3390/nu9121348
|View full text |Cite
|
Sign up to set email alerts
|

Short Chain Fatty Acids in the Colon and Peripheral Tissues: A Focus on Butyrate, Colon Cancer, Obesity and Insulin Resistance

Abstract: Increased dietary fiber consumption has been associated with many beneficial effects, including amelioration of obesity and insulin resistance. These effects may be due to the increased production of short chain fatty acids, including propionate, acetate and butyrate, during fermentation of the dietary fiber in the colon. Indeed, oral and dietary supplementation of butyrate alone has been shown to prevent high fat-diet induced obesity and insulin resistance. This review focuses on sources of short chain fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
268
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(281 citation statements)
references
References 208 publications
(372 reference statements)
6
268
0
7
Order By: Relevance
“…Depletion of butyrate is associated with impaired intestinal barrier integrity 62 , and loss of intestinal barrier function is in turn associated with a growing number of inflammatory disease states diseases, including obesity as well as autoimmune diseases and cancer (reviewed in 63,64 ). While butyrate was not directly measured in the present study, decreased levels of butyrate and other SCFA are widely reported in the context of obesity while high-fiber plant products are known to increase colonic fermentation and the generation of SCFA 65 .…”
Section: Discussionmentioning
confidence: 67%
“…Depletion of butyrate is associated with impaired intestinal barrier integrity 62 , and loss of intestinal barrier function is in turn associated with a growing number of inflammatory disease states diseases, including obesity as well as autoimmune diseases and cancer (reviewed in 63,64 ). While butyrate was not directly measured in the present study, decreased levels of butyrate and other SCFA are widely reported in the context of obesity while high-fiber plant products are known to increase colonic fermentation and the generation of SCFA 65 .…”
Section: Discussionmentioning
confidence: 67%
“…Decreased plasma glucose in response to butyrate supplementation is consistent with other studies (Neogrady et al, 1989;Huhtanen et al, 1993;Herrick et al, 2018), although the mechanism is not fully understood. In nonruminants, evidence indicates that butyrate has a regulatory role in glucose and lipid metabolic pathways in multiple tissues (reviewed by McNabney and Henagan, 2017). Similarly, glucose synthesis from propionate was inhibited by butyrate in sheep hepatocytes (Demigne et al, 1986;Aiello et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fiber forms gels in the stomach that slows down starch digestion and gastric emptying which subsequently increase satiety (Yu, Ke, Li, Zhang, & Fang, 2014). Due to inability of both salivary and pancreatic α‐amylase to break down fiber, fiber reaches the colon where they are fermented by colonic bacteria to produce short‐chain fatty acids such as butyrate, acetate, and propionate which have other physiological function such as regulating satiety (Byrne, Chambers, Morrison, & Frost, 2015; McNabney & Henagan, 2017). Butyrate and acetate have been shown to upregulate genes involved in fatty acid oxidation (Canfora, Jocken, & Blaak, 2015), inducing lipolysis in adipocytes (Rumberger, Arch, & Green, 2014), which is important in initiating weight loss in overweight persons.…”
Section: Effect Of Germination or Malting On Nutrients And Mineralsmentioning
confidence: 99%